y-(-7)=17⋅(x-(-7))

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Multiply -1 by -7.

y+7=17⋅(x-(-7))

Simplify 17⋅(x-(-7)).

Multiply -1 by -7.

y+7=17⋅(x+7)

Apply the distributive property.

y+7=17x+17⋅7

Combine 17 and x.

y+7=x7+17⋅7

Cancel the common factor of 7.

Cancel the common factor.

y+7=x7+17⋅7

Rewrite the expression.

y+7=x7+1

y+7=x7+1

y+7=x7+1

Move all terms not containing y to the right side of the equation.

Subtract 7 from both sides of the equation.

y=x7+1-7

Subtract 7 from 1.

y=x7-6

y=x7-6

Rewrite in slope-intercept form.

y=17x-6

y=17x-6

Using the slope-intercept form, the slope is 17.

m=17

Find the Slope y-(-7)=1/7*(x-(-7))